Overlapping borders. Images of East Belgium as a transcultural area in contemporary East Belgian literature - Beck, Philippe; Penné, Lesley (Oxford German Studies, 2019)
„In this contribution, we discuss how the East Belgian authors Hannes Anderer, Freddy Derwahl and Leo Wintgens represent history, borders and multilingualism in their novels. These contemporary authors have understood that coming to terms with the past is an important aspect in developing a genuine East Belgian collective identity. Furthermore, the multiple borders (with Germany, the Netherlands and Luxembourg) and the co-existence of several languages in this region have become constitutive of collective self-understanding, also with regard to the construction of a region-specific cultural memory. Finally, we show the narrative strategies used in the novels Unterwegs zu Melusine (2006), Bosch in Belgien (2006) and Wege aus Sümpfen. Roman einer Grenzlandschaft Teil I (2001) and Teil II (2006) in order to bring to bear the relation between minority and majority culture by recurring to imagology.“
Keywords: Annexion; Geschichtsbild; Geschichtsschreibung; Kulturelle Identität; Mehrsprachigkeit; Schriftsteller; Staatsgrenze

Generational Conflicts, the Spirit of ‘68 and Cultural Emancipation in the German Speaking Community of Belgium. A Historical Essay About the ‘73 Generation - Fickers, Andreas (Borderland Studies meets Child Studies. A European Encounter, 2018)
„Veränderungen lagen in der Luft – so könnte man die gesellschaftliche Stimmung Ende der 1960er, Anfang der 1970er Jahre wohl am besten beschreiben. International trat der Generationenkonflikt zwischen der Nachkriegsgeneration, den so genannten ‘Baby-Boomern’, und jener Generation, die den Zweiten Weltkrieg als Jugendliche oder junge Erwachsene erlebt hatten, in Form von Studentenprotesten, Anti-Kriegsbewegungen und neuen Lebensentwürfen zutage. Es ist wohl kaum ein Zufall, dass sich zu dieser Zeit auch in Ostbelgien der Protest regte. Oder doch? Wogegen lehnten sich die ‘jungen Wilden’ im deutschsprachigen Belgien auf? Vom Geist der ‘68er beseelt, so die These, schlugen vor allem junge Eifler neue Töne an, die die politische Landschaft – mehr denn die sozialen oder kulturellen Milieus Ostbelgiens – nachhaltig prägen sollte.“
Keywords: Achtundsechziger; Generationskonflikt; Kulturelle Identität; Protestbewegung; Vergangenheitsbewältigung

„“L’identité des Belges germanophones est une non-identité“. Quelques réflexions à propos de publications récentes sur l’histoire de la Communauté germanophone de Belgique - Brüll, Christoph (BEG-CHTP, 2009)
Keywords: Deutschsprachige Gemeinschaft; Kulturelle Identität; Nationalbewusstsein; Ostbelgien; Regionale Identität